(3EOGQI GdJZjjQ HfLGMs (3GSJNOGe GdfXQjI hGdNHQI aj JfajP GdJZjjQs - (3hdjeR(B, (3GdGfs; (3SGdjs ((3GdQjGVs (3OGQ GdeQjN ddfTQs, 2004)
(3GdJYde(B-(3hGdfeGPL GdPgfjI(B-(3hGdMGdGJ GdJGQjNjI(B-(3GdJZjjQ GdJfXjej GdCSGSj(B-(3JWhjQ JhLg GdJShjb(B-(3Jbdjd GdMLe(B-(3hGdGSJYGfI HGdeUGOQ GdNGQLjI(B-(3EYGOI JfXje NOeGJ GdOYe(B-(3OeL GdJfXjeGJ(B-(3JcGed JbfjI GdeYdheGJ aj GdCYeGd(B-(3GdJZjjQ ZjQ GdeNWW aj hcGdI GHMGK GdShb(B-(3JWhjQ fehPL TNUj dJfajP GdJZjjQ(B-(3caGAGJ GdEOGQI GdMQLI(B-(3JHUQGJ ef NdGd GdfXQjI(B:(3GcJSGH GdJYGhf(B-(3JHUQGJ ef NdGd GdfXQjI(B:(3EOGQI GdELgGO(B-(3JYdjbGJ fgGFjI(B:(3JWhjQ GdbjGOI GdaYGdI aj JfajP GdJZjjQs
Keywords: (3GdJfejI GdGOGQjIs